A rare case of Wild-Type GIST of descending colon with GANT characteristics - Kalliouris, Dimitrios N.; Nikou, Efstathios; Zaravinos, Spiridon; Manesis, Konstantinos; Oikonomou, Christianna; Lingria, Antonina; Karameris, Andreas; Alexandrakis, Georgios; Skandalakis, Panagiotis; Filippou, Dimitrios (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Kalliouris DN, Nikou E, Zaravinos S, Manesis K, Oikonomou C, Lingria A, et al. A rare case of Wild-Type GIST of descending colon with GANT characteristics. Turk J Gastroenterol 2019; 30(6): 573-5